Compact Broadband Circularly Polarized CPW-Fed Antenna with Characteristic Mode Analysis - Wei Xu; Jingchang Nan; Mingming Gao (International Journal of Antennas and Propagation)
A compact circularly polarized (CP) antenna is proposed for low-profile and wideband operation based on characteristic mode analysis (CMA). A ring patch with a gap and two arc-shaped metallic stubs as the radiator is analyzed and optimized by CMA to figure out the orthogonal modes and operating frequency band for potential good axial ratio (AR) performance. The studies of these CP modes provide a physical insight into the property of broadband circular polarization. Such an in-depth understanding paves the way for the proposal of novel CP antenna with separation between the design of radiator and feeding network. A 50-Ω coplanar waveguide (CPW) is introduced and placed appropriately to excite the desired modes based on the information from CMA, which employs two asymmetric ground planes to improve the performance in terms of AR and impedance matching. The antenna with a compact size of 0.71λ0 × 0.76λ0 × 0.038λ0 (λ0 is the free-space wavelength at the center frequency of the 3-dB AR bandwidth) is fabricated and measured for validation. The realized gain varies from 1.6 to 3.1 dBic over the operating bandwidth characterized by the measured 10-dB impedance bandwidth of 83.8% (3.98–9.72 GHz) and 3-dB AR bandwidth of 70.3% (4.59–9.57 GHz), respectively.